The influence of host receptivity and conformity pressure on the intercultural transformation of Filipino migrants in New Zealand - Separa LAC; Croucher SM; Hodis GM; Feekery A (Elsevier B.V., 2024)
Filipinos are the second fastest-growing Asian population working in dairy farming, healthcare, construction, and other industries in New Zealand. Like other immigrants, Filipinos experience basic and advanced intercultural transformation as they communicate and interact with people in the country. Croucher and Kramer's cultural fusion theory proposes a positive relationship between host receptivity and intercultural transformation and a negative relationship between host conformity pressure and intercultural transformation. Employing a survey of 315 Filipino migrants in New Zealand, this study addresses the extent to which host receptivity and host conformity pressure affect intercultural transformation. Regression analysis is used to assess the hypotheses and research question. Results reveal both host receptivity and host conformity pressure have positive relationships with intercultural transformation. The potential role of media and Filipino values in this study are also discussed.
Keywords: Acculturation; Adaptation; intercultural changes; Host receptivity; Host conformity pressure